Regulation of eukaryotic elongation factor 1 alpha (eEF1A) by dynamic lysine methylation. Issue 3 (4th March 2018) - Jakobsson, Magnus E.; Małecki, Jędrzej; Falnes, Pål Ø.
ABSTRACT: Lysine methylation is a frequent post-translational protein modification, which has been intensively studied in the case of histone proteins. Lysine methylations are also found on many non-histone proteins, and one prominent example is eukaryotic elongation factor 1 alpha (eEF1A). Besides its essential role in the protein synthesis machinery, a number of non-canonical functions have also been described for eEF1A, such as regulation of the actin cytoskeleton and the promotion of viral replication. The functional significance of the extensive lysine methylations on eEF1A, as well as the identity of the responsible lysine methyltransferases (KMTs), have until recently remained largely elusive. However, recent discoveries and characterizations of human eEF1A-specific KMTs indicate that lysine methylation of eEF1A can be dynamic and inducible, and modulates mRNA translation in a codon-specific fashion. Here, we give a general overview of eEF1A lysine methylation and discuss its possible functional and regulatory significance, with particular emphasis on newly discovered human KMTs.